2020
DOI: 10.1371/journal.pone.0233055
|View full text |Cite
|
Sign up to set email alerts
|

Response of cytokinins and nitrogen metabolism in the fronds of Pteris sp. under arsenic stress

Abstract: Given the close relationship between cytokinins (CKs), photosynthesis and nitrogen metabolism, this study assessed the effect of arsenic (As) contamination on these metabolic components in the As-hyperaccumulators Pteris cretica L. var. Albo-lineata (Pc-A) and var. Parkerii (Pc-P) as well as the As-non-hyperaccumulator Pteris straminea Mett. ex Baker (Ps). The ferns were cultivated in a pot experiment for 23 weeks in soil spiked with As at the levels 20 and 100 mg�kg-1. For the purpose of this study, the CKs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
5
16
0
Order By: Relevance
“…In the present study, As content in Pc-Al was > 1 000 mg/kg, whereas As content in Pc-Pa was under the limit of hyperaccumulation (Table 1). Similar results for Pc-Pa were shown in our previous study (Pavlíková et al 2020), as well as for Pc-Al (Zemanová et al 2020). In contrast to our results, Luongo and Ma (2005) determined As content in Pc-Pa > 1 000 mg/kg and identified this fern as an As-hyperaccumulator.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, As content in Pc-Al was > 1 000 mg/kg, whereas As content in Pc-Pa was under the limit of hyperaccumulation (Table 1). Similar results for Pc-Pa were shown in our previous study (Pavlíková et al 2020), as well as for Pc-Al (Zemanová et al 2020). In contrast to our results, Luongo and Ma (2005) determined As content in Pc-Pa > 1 000 mg/kg and identified this fern as an As-hyperaccumulator.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, our results showed a decrease in the GLU/GLN ratio by As treatment in fronds of Pc-Al and Pc-Pa (Figure 2). Similarly, in our previous study, GLU/GLN ratio decreased with As levels in fronds of Pc-Al and Pc-Pa, which indicated a negative As effect by depletion of the C pool as a source for the biosynthesis of other free AAs (Pavlíková et al 2020).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results of As bioaccumulation and translocation confirmed P. cretica ‘Albo-lineata’ as an As-hyperaccumulating fern. Similar results were previously observed [ 21 , 23 , 28 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%